PEMANFAATAN DISRUPSI DIGITAL DALAM DIMENSI INTERAKSI, KOMUNIKASI DAN FLESIBELITAS PEMBELAJARAN ON LINE ERA REVOLUSI INDUSTRI 4.0 - Ridhuan, Syamsu (Eduscience : Jurnal Ilmu Pendidikan, 2020)
PEMANFAATAN DISRUPSI DIGITAL DALAM DIMENSI INTERAKSI, KOMUNIKASI DAN FLESIBELITAS PEMBELAJARAN ON LINE ERA REVOLUSI INDUSTRI 4.0 Syamsu Ridhuan1, Aliaras Wahid2, Silvia Ratna Juwita31FKIP, 2Fakultas Ilmu Komunikasi, dan 3Fakultas Ilmu KomputerUniversitas Esa UnggulJalan Arjuna Utara Nomor 9, Kebon Jeruk, Jakarta - 11510syamsu@esaunggul.ac.id Abstract Massive and fundamental changes from the old manual system to the all-digital system make a shift in life, including in the field of education. Changes occur due to the impact of digital disruption that is sweeping people in the era of industrial revolution 4.0. Digital disruption encourages the process of educational interaction activities that are different from conventional learning systems, face to face. Online learning communication as a whole uses modules, learning video recordings, e-book / e-journal links as enrichment material that is transformed through learning media e-learning accounts that are connected to students. There is feedback to lecturers through discussion forums, working on quizzes and online assignments. Flexibility concerns the perspective of time, place and funding of learning programs. Directly impacts students in the process and completion of education. Quantitative research methods, through a survey approach with questioner research instruments and using the Google form facility. Data were analyzed descriptively, interpreted and discussed in the research findings. The conclusion turns out that the existence of digital disruption is significantly effective in the dimensions of interaction, communication and flexibility of online learning. It is recommended that each university be able to take advantage of the impact of digital disruption by opening e-learning programs according to their respective fields of excellence. Keywords: educational interactions, learning communication, e-learning flexibility